PENGGUNAAN MEDIA LITERASI DIGITAL UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS II SD NEGERI JEUNIEB - Nurmina; Nailus Saa’dah (Jurnal Binagogik, 2025)
This research is motivated by the low reading ability of students, which is characterized by difficulties in spelling, distinguishing letters, and a lack of interest in reading due to monotonous and less interesting learning methods. This study aims to improve reading skills, increase student and teacher activity, and determine the responses of second-grade students at SD Negeri 5 Jeunieb through the use of digital literacy media. This research method uses a qualitative approach with a type of classroom action research (CAR) implemented in two cycles, consisting of planning, implementation, observation, and reflection stages. The research data consisted of test results, observation results, and questionnaire results, with 14 second-grade students at Jeunieb 5 Elementary School as the data source. Data collection techniques were carried out through tests, observations, and questionnaires. The results showed that the use of digital literacy media can improve the reading skills of second-grade students at Jeunieb 5 Elementary School. This is evident from the results of student learning completion in cycle I reaching 64% increasing in cycle II increasing to 85%. In addition, in terms of the learning process, the average results of student observations in cycle 1 and cycle II were obtained 92.90% with a very good category, while the results of teacher observations obtained an average score of cycle I was 97.5% and 96.2 with a very good category. Furthermore, in terms of student responses, the answer obtained was that the use of digital literacy media was proven effective in improving elementary school students' reading skills, as well as being able to create a more interactive and enjoyable learning atmosphere.